Engineered combinatorial cell device for wound healing and bone regeneration - Kadunc Polajnar, Lucija; Lainšček, Duško; Gašperšič, Rok; Sušjan-Leite, Petra; Kovačič, Uroš; Butinar, Miha; Turk, Boris; Jerala, Roman; Hafner-Bratkovič, Iva (Frontiers in Bioengineering and Biotechnology, 2023)
Growth factors are key regulators that promote tissue regeneration and healing processes. While the effects of individual growth factors are well documented, a combination of multiple secreted growth factors underlies stem cell-mediated regeneration. To avoid the potential dangers and labor-intensive individual approach of stem cell therapy while maintaining their regeneration-promoting effects based on multiple secreted growth factors, we engineered a “mix-and-match” combinatorial platform based on a library of cell lines producing growth factors. Treatment with a combination of growth factors secreted by engineered mammalian cells was more efficient than individual growth factors or even stem cell-conditioned medium in a gap closure assay. Further, we implemented in a mouse model a device for allogenic cell therapy for an in situ production of growth factors, where it improved cutaneous wound healing. Augmented bone regeneration was achieved on calvarial bone defects in rats treated with a cell device secreting IGF, FGF, PDGF, TGF-β, and VEGF. In both in vivo models, the systemic concentration of secreted factors was negligible, demonstrating the local effect of the regeneration device. Finally, we introduced a genetic switch that enables temporal control over combinations of trophic factors released at different stages of regeneration mimicking the maturation of natural wound healing to improve therapy and prevent scar formation.